Responses of 'Spring Bright' and 'Summer Bright' nectarines to deficit irrigation: Fruit growth and concentration of sugars and organic acids - Thakur, Anirudh; Singh, Zora (Elsevier, 2012)
The effects of deficit irrigation (DI) during pit hardening on fruit mass and levels of individual sugars and organic acids during fruit maturation were investigated in ‘Spring Bright’ and ‘Summer Bright’ nectarines. Apart from control irrigation (CI), there were three DI levels viz. DI 75 (75% CI), DI 58 (58% CI) and DI 33 (33% DI). All the DI treatments significantly decreased mid-day stem water potential and volumetric soil water content in both cultivars. DI 75 had no significant effect on fruit mass at harvest. DI 33 and DI 58 reduced fruit mass at harvest in ‘Spring Bright’ (17.22 and 8.20%, respectively) as well as ‘Summer Bright’ (8.88 and 9.42%, respectively). DI 33 increased levels of total sugars and sucrose during fruit maturation in both cultivars. In ‘Spring Bright’, all the DI treatments increased glucose levels until 72 days after fruit set (DAFS) later on, decreased until harvest, whereas, DI increased glucose concentration in ‘Summer Bright’. DI 33 treatment decreased the level of total acids and malic acid during fruit growth and maturation in both cultivars. In conclusion, DI 75 did not affect fruit mass, sugars and organic acids in both cultivars. DI 33 and DI 58 increased accumulation of total sugars, sucrose and sorbitol in both cultivars with acceptable fruit mass (>85 g). Severe DI treatment (DI 33) decreased glucose and fructose at harvest in ‘Spring Bright’ but, increased glucose in ‘Summer Bright’.